PERAN POLA LATIHAN FISIK DALAM MENINGKATKAN PERFORMA SPRINT DAN KELINCAHAN PEMAIN SSB SANGAR MUDA - Muhammad Ramanto; Deka Ismi Mori Saputra (Master of Physical Culture and Recreation in Nusantara, 2025)
The performance improvement of youth soccer players is greatly affected by the physical training patterns implemented, especially in sprint speed and agility. At SSB Sangar Muda, the training program is still general and not yet structured to specifically develop sprint and agility skills. This study aims to explore the role of physical training in enhancing players’ sprint and agility performance and to examine factors influencing training effectiveness. Using a qualitative case study method, data were collected from one coach and five players through in-depth interviews. The focus was on players’ experiences and perceptions of training, as well as the coach’s strategies in planning programs. Data were analyzed descriptively to provide systematic findings. The results show that the physical training applied remains general, with sprint training limited, leading to less optimal acceleration and maximum speed. Agility training has supported balance and movement to avoid opponents, but has not sufficiently improved players’ reflexes in real match conditions. These findings indicate the importance of designing more specific, structured, and varied training programs to better develop sprint and agility performance among youth soccer players at SSB Sangar Muda.